Why environmental consciousness does not affect intention to buy? - Benita Benyamin; Dergibson Siagian (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2021)
Environmental consciousness arises when there is an understanding of the need for a balance between life and nature. This study aims to investigate whether such consciousness affects purchasing behavior of environmental-friendly claimed products directly or through their interaction with a price. To answer this question, the authors recruited 100 consumers as respondents who met the authors' predetermined requirements. The data analyzed using structural equation modeling reveals that environmental consciousness does not affect purchase intention, but the price does. It is also found to have no interaction with the price in influencing behavioral intention. This result leaves a question that further researchers can answer. Study in different product categories is encouraged. Original Article | Turnitin